Socio-Cultural Development in Judo Athletes - Berliana Berliana; Ira Purnamasari; Geraldi Novian (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
This study aims to develop the socio-culture of Judo athletes. Judo provides socio-cultural values to each individual involved through the training process that is carried out, these socio-cultural values are expected to remain in the daily life of Judo athletes. This study used an experimental method with a one-group pretest-posttest design research design. The treatment carried out during the experiment was an integration of socio-cultural value education with the Judo training process. Treatment is given for 6 weeks with a frequency of 2 sessions/week, each session consisting of 120 minutes divided into 5 parts, namely introduction, explanation, discussion, ice breaking, and closing. The sample used in this study was 10 athletes from Bandung PPLPD Judo by using a total sampling approach. The instrument that the author uses in this study is the TQR-Questionnaire which is given twice to the sample. The results showed that there was a significant influence between Judo training and the increase in social-cultural values of athletes. This indicates that Judo training can be included in instilling socio-cultural values, especially in Judo athletes.